IMPLEMENTASI KARTU TANI DALAM PENYALURAN PUPUK BERSUBSIDI DI DESA BENTENG PALIOI KECAMATAN KINDANG KABUPATEN BULUKUMBA PERSPEKTIF SIYASAH SYAR'IYYAH - Ayu, Nurelvia Trisna; Ilyas, Musyfikah; Istiqamah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to describe the Implementation of Farmer Cards in the Distribution of Subsidized Fertilizers in Benteng Palioi Village, Kindang District, Bulukumba Regency. In answering these problems, the author uses a normative syar`i approach and an empirical juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results showed that during the distribution of subsidized fertilizers using farmer cards, it was not implemented perfectly, because there were still many problems experienced by farmers in applying farmer cards, such as lack of service in card printing, lack of socialization which made it difficult for farmers to use farmer cards, and lack of farmer funds in activating farmer cards and these cards have not been distributed evenly. Supporting and inhibiting factors faced by farmers in the field in the implementation of farmer cards are supporting factors that can facilitate distributors in preparing reports, and can obtain fertilizer easily, but this farmer card also has obstacles in its application, namely the lack of good coordination between farmer groups and distributors, the limited ability of farmers to access program services. Basically, Siyasah Syar'iyyah's view of implementing farmer cards in the distribution of subsidized fertilizers is that the government must be more responsible and must uphold the values of justice and the government must do its job well in making policies that will bring benefit to its people